2018
DOI: 10.1021/acs.jafc.8b02178
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin: A Multifunctional Molecule That Triggers Defense Responses against High Light and Nitrogen Starvation Stress in Haematococcus pluvialis

Abstract: Melatonin (MLT), a ubiquitously distributed small molecule, functions in plant responses to various biotic and abiotic stresses. However, the interactions between melatonin and other important molecules in Haematococcus pluvialis response stresses are largely unknown. In the present study, exogenous melatonin improved H. pluvialis resistance to nitrogen starvation and high light. We concluded that exogenous melatonin treatment prevented the reactive oxygen species (ROS) burst and limited cell damage induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(39 citation statements)
references
References 58 publications
(100 reference statements)
0
39
0
Order By: Relevance
“…), and stimulated the highest accumulation of astaxanthin in Haematococcus pluvialis (Ding et al. ). Unlike the effects of N starvation on lipids and astaxanthin, algal protein content was reported to be reduced dramatically in H. pluvialis upon N starvation (Zhao et al.…”
mentioning
confidence: 99%
“…), and stimulated the highest accumulation of astaxanthin in Haematococcus pluvialis (Ding et al. ). Unlike the effects of N starvation on lipids and astaxanthin, algal protein content was reported to be reduced dramatically in H. pluvialis upon N starvation (Zhao et al.…”
mentioning
confidence: 99%
“…Haemaococcus lacustris is not only able to produce a substantial amount of TAG but also the highest content of AST under stress conditions, which represents a leading algal candidate of industrial potential [29][30][31][32][33][34][35]. For example, HL and ND stresses can effectively promote the accumulation of AST and TAG in H. lacustris [32][33][34][50][51][52][53]. Our results also revealed that (1) T-AST and T-TAG contents signi cantly increased under HL-W, HL-B, 1/4N, HL-W+1/4N, and HL-B+1/4N conditions, respectively, which was consistent with previous study [34,41], (2) M-AST was the main form which is also proven by previous studies [36][37][38][39], (3) compared to ND stress, HL was more effective in inducing AST accumulation especially under the blue HL condition, which has been testi ed in our previous study [50], (4) coupled HL and ND dual stimulation might be better choices in improving AST and TAG accumulation in H. lacustris ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…AST/TAG accumulation and HpDGAT2 genes transcription expression upon HL and ND stresses High light (HL) and nitrogen de cient (ND) stresses can effectively promote the accumulation of AST and TAG in H. lacustris [32][33][34][50][51][52][53]. To understand the relationship between HpDGAT2s expression and TAG/AST biosynthesis, time-course patterns of algal biomass, transcription expression, total AST (T-AST), and total TAG (T-TAG) contents in photoautotrophic cultures of H. lacustris under HL, ND, and double HL+ND stresses were studied ( Fig.…”
Section: Molecular Cloning and Bioinformatics Analysis Of Hpdgat2s Genesmentioning
confidence: 99%
“…The resistance of the chlorophyte (green algae) Haematococcus pluvialis to nitrogen starvation or light stress was improved by exogenous melatonin. Melatonin-induced the accumulation of the H. pluvialis activated NO-dependent MAPK signal cascade, indicating that MAPK is a target of NO action in physiological processes [33]. The physiological pathways involving stress-related transcription factors remain to be further studied.…”
Section: Other Stressesmentioning
confidence: 98%